Genetic variants regulating ORMDL3 expression contribute to the risk of childhood asthma. - Moffatt, M; Kabesch, M; Liang, L; Dixon, A; Strachan, D; Heath, S; Depner, M; von Berg, A; Bufe, A; Rietschel, E; Heinzmann, A; Simma, B; et al. (2007)
Asthma is caused by a combination of poorly understood genetic and environmental factors. We have systematically mapped the effects of single nucleotide polymorphisms (SNPs) on the presence of childhood onset asthma by genome-wide association. We characterized more than 317,000 SNPs in DNA from 994 patients with childhood onset asthma and 1,243 non-asthmatics, using family and case-referent panels. Here we show multiple markers on chromosome 17q21 to be strongly and reproducibly associated with childhood onset asthma in family and case-referent panels with a combined P value of P < 10(-12). In independent replication studies the 17q21 locus showed strong association with diagnosis of childhood asthma in 2,320 subjects from a cohort of German children (P = 0.0003) and in 3,301 subjects from the British 1958 Birth Cohort (P = 0.0005). We systematically evaluated the relationships between markers of the 17q21 locus and transcript levels of genes in Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines from children in the asthma family panel used in our association study. The SNPs associated with childhood asthma were consistently and strongly associated (P < 10(-22)) in cis with transcript levels of ORMDL3, a member of a gene family that encodes transmembrane proteins anchored in the endoplasmic reticulum. The results indicate that genetic variants regulating ORMDL3 expression are determinants of susceptibility to childhood asthma.